The Problem of Increasing Interest in the Russian Language at Universities (Eurasian Journal of Learning and Academic Teaching, 2022)
The development of the cognitive interests of the student in the process of his education in the lower courses is one of the most important factors in the success of learning in university. All the efforts of the teacher to form in students any idea or concept is doomed to failure if the students fail to interest the subjects of reasoning